Induction of Apoptosis by Hypertension Via Endoplasmic Reticulum Stress - Yingying Sun (Kidney & Blood Pressure Research, 2015)
Background/Aims: Endoplasmic reticulum (ER) stress is one of the intrinsic apoptosis pathways, and cardiac apoptosis can occur in cardiovascular diseases, such as hypertension. However, the mechanisms by which ER stress leads to apoptosis remain enigmatic, particularly in the progression from cardiac hypertrophy to diastolic heart failure due to hypertension. Methods: We used spontaneously hypertensive rats (SHRs) to investigate possible signalling pathways for ER stress. Results: We found that cardiac protein and mRNA levels of glucose-regulated protein 78 were up-regulated. In addition, the CHOP- and caspase-12-dependent pathways, but not that of JNK, were activated in the SHR rats. Conclusions: These results suggest that ER stress can contribute to myocardial apoptosis during hypertensive disease.